Chitosan/bioactive glass nanoparticle composite membranes for periodontal regeneration - Mota, Joana (2012)
Barrier membranes are used in periodontal applications with the aim of supporting periodontal regeneration by physically blocking migration of epithelial cells. The present work proposes a combination of chitosan (CHT) with bioactive glass nanoparticles (BG-NPs) in order to produce a novel guided tissue and bone regeneration membrane, fabricated by solvent casting. The CHT/BG-NP nanocomposite membranes are characterized in terms of water uptake, in mechanical tests, under simulated physiological conditions and in in vitro bioactivity tests. The addition of BG-NPs to CHT membranes decreased the mechanical potential of these membranes, but on the other hand the bioactivity improved. The membranes containing the BG-NPs induced the precipitation of bone-like apatite in simulated body fluid (SBF). Biological tests were carried out using human periodontal ligament cells and human bone marrow stromal cells. CHT/BG-NP composite membranes promoted cell metabolic activity and mineralization. The results indicate that the CHT/BG-NP composite membrane could potentially be used as a temporary guided tissue regeneration membrane in periodontal regeneration, with the possibility to induce bone regeneration.